Assessing the shear behavior of mixed waste materials from Semakau island: a large direct shear test study - Ma, Congcong (Nanyang Technological University, 2024)
This study offers an in-depth examination of the shear behaviour of mixed waste materials from Semakau Island, utilizing large-scale direct shear tests under various normal stresses of 100kN, 200kN, and 400kN. It evaluates the mechanical characteristics of Mixed Materials (MM) and Mixed Materials with Concrete (MC) interfaces to understand their shear strength. Aimed at exploring the potential for sustainable construction applications, the study systematically investigates the mechanical characteristics of waste materials, focusing on parameters such as friction angle and shear strength. The observed increments in shear strength for MC over the MM under various normal stresses show a significant range, from as low as 1.7% to as high as 41.4%. However, sample C9E1 stands out exceptionally, showcasing the significant influence of lower moisture content. Additionally, the untreated sample C9B13N provides further support, emphasizing the critical role of low water content in enhancing shear strength. This study also emphasizes the influence of shear strength material under various combinations of factors such as normal stresses, moisture content, particle size distribution, and relative density. The results suggest that mixed waste soil, through its interaction at the concrete interface, demonstrates enhanced strength properties. Such improvement is credited to the effective bonding between the waste soil and concrete. Consequently, these attributes make waste soil a suitable candidate for construction uses, such as fill material for concrete caissons.